1998
DOI: 10.1073/pnas.95.13.7760
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotides against α 1E reduce R-type calcium currents in cerebellar granule cells

Abstract: Many neurons of the central nervous system display multiple high voltage-activated Ca 2؉ currents, pharmacologically classified as L-, N-, P-, Q-, and R-type. Of these current types, the R-type is the least understood. The leading candidate for the molecular correlate of R-type currents in cerebellar granule cells is the ␣ 1E subunit, which yields Ca 2؉ currents very similar to the R-type when expressed in heterologous systems. As a complementary approach, we tested whether antisense oligonucleotides against ␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 44 publications
3
58
0
Order By: Relevance
“…Cerebellar granule neurons (CGN) and hippocampal neurons were cultured as previously reported (32,33). In brief, one cerebellum from a 5-to 7-day-old mouse (or 2 hippocampi from a 0 -1 day old) was removed and washed in modified Hanks' balanced salt solution (HBSS) (Sigma, St. Louis, MO).…”
Section: Cell Culturementioning
confidence: 99%
“…Cerebellar granule neurons (CGN) and hippocampal neurons were cultured as previously reported (32,33). In brief, one cerebellum from a 5-to 7-day-old mouse (or 2 hippocampi from a 0 -1 day old) was removed and washed in modified Hanks' balanced salt solution (HBSS) (Sigma, St. Louis, MO).…”
Section: Cell Culturementioning
confidence: 99%
“…To enhance uptake into the cells, three bases at the ends of the ODNs were modified to contain phosphorothioate bonds (Pilowsky et al, 1994). Previous studies have demonstrated that the treatment of cerebellar cells in culture with these modified ODNs reduces the levels of targeted proteins without altering cell viability (Piedras-Renteria and Tsien, 1998;Kumar et al, 2001). The probes had the following sequences: Smad1 ODN, 5Ј-TGAAAACAAGTGGTCA-3Ј; and SMAD4 ODN, 5Ј-CTGTGGCACATCAAACT-3Ј.…”
Section: Tissue Culturementioning
confidence: 99%
“…Figure 2 Detection of sense and antisense a1E cassettes by RT-PCR in stably transfected INS-1 cell clones. The full-length cDNA of sense and antisense cassettes was amplified after reverse transcription (see lanes with '+') of total RNA from four antisense (lanes 2-9) and two sense clones (lanes [11][12][13][14]. Temperature and cycle number were selected to obtain optimal conditions for a selective amplification of only overexpressed transcripts.…”
Section: Overexpression Of A1e Cassettes After Stable Transfection Ofmentioning
confidence: 99%
“…Using antisense a1E oligonucleotides and the a1E-selective antagonist SNX-482, it was shown that a1E is related to multiple resistant components of HVA Ca 2+ channels in rat cerebellar granule cells (12,13). Some, but not all of the resistant component is absent in a1E-depleted cerebellar granule cells isolated from a1E knockout mice (14).…”
Section: Introductionmentioning
confidence: 99%